Chemical Bonding in Polarised Push–Pull Ethylenes. Issue 26 (24th May 2019) - Yanai, Hikaru; Suzuki, Takumi; Kleemiss, Florian; Fukaya, Haruhiko; Dobashi, Yasuo; Malaspina, Lorraine A.; Grabowsky, Simon; Matsumoto, Takashi
Abstract: 1, 1‐Diamino‐2, 2‐bis(triflyl)ethylenes with both twisted and planar structures around the partial "C=C" bond were synthesised. Bonding properties in these compounds were analysed by an experimental approach using high‐resolution X‐ray diffraction data treated with X‐ray wavefunction refinement (XWR). In the twisted compound, a dominant contribution of the charge‐separated resonance structure was revealed. On the contrary, the nearly planar compound still showed π‐bonding character, however, with a considerable contribution of the charge‐separated resonance structure. Abstract : Twist and shout : 1, 1‐Diamino‐2, 2‐bis(triflyl)ethylenes with both twisted and planar structures around the partial "C=C" bond were synthesised. In both compounds, the bonding properties of the central C−C bonds were analysed using high‐resolution X‐ray diffraction data treated with X‐ray wavefunction refinement (XWR).